Educational mismatch and mobility - Christiane Roller; Christian Rulff; Michael M. Tamminga (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
With increasing educational attainment in Germany, the issue of inefficient human capital allocation gains importance. Especially overeducation seems to be a problem, since more and more highly educated individuals are required to take jobs that do not match their educational level, settling for lower wages than their peers. This raises the question, how these individuals perform in these jobs and whether they have an advantage compared to their adequately educated colleagues performing the same job. The career mobility model suggests that this is indeed the case, with overeducated workers being more prone to take up on-the-job training, to climb up the career ladder, or to eventually leave to professions more suitable to their educational level. Our empirical analysis, using the German SOEP, confirms this theory for Germany. We find that overeducated workers have a significantly higher probability to take up on-the-job training than adequately educated workers and, at least in certain jobs, have a higher probability to move to jobs that better match their educational level. Furthermore, we find that overeducated workers experience higher wage growth than their colleagues in all job types. – – Mit steigendem Bildungsgrad gewinnt das Problem der ineffizienten Humankapitalallokation in Deutschland immer mehr an Bedeutung. Besonders Überqualifikation scheint ein Problem zu sein, da immer mehr hoch qualifizierte Personen Jobs annehmen, die nicht ihrem Bildungsniveau entsprechen und sich mit geringeren Löhnen zufriedengeben als adäquat qualifizierte Arbeitnehmer. Dies wirft die Frage auf, wie diese Personen in ihren Berufen abschneiden und ob sie einen Vorteil gegenüber ihren adäquat qualifizierten Kollegen in der gleichen Tätigkeit haben. Nach dem "Career Mobility Model" ist dies in der Tat der Fall, da überqualifizierte Arbeitskräfte mit höherer Wahrscheinlichkeit an innerbetrieblichen Weiterbildungsmaßnahmen teilnehmen, beruflich aufsteigen, oder in einen an ihre entsprechende Qualifikation angepassten Beruf übergehen. Unsere empirische Analyse unter Verwendung des SOEP kann diese Theorie für Deutschland bestätigen. Wir stellen fest, dass überqualifizierte Arbeitskräfte eine deutlich höhere Wahrscheinlichkeit aufweisen an betrieblichen Weiterbildungsmaßnahmen teilzunehmen. Außerdem zeigt sich zumindest in bestimmten Berufen, dass Überqualifikation im Vergleich zu adäquater Qualifikation mit einer erhöhten beruflichen Aufwärtsmobilität einhergeht. Darüber hinaus stellen wir fest, dass überqualifizierte Arbeitnehmer in allen Beschäftigungsarten einen höheren Lohnzuwachs als ihre Arbeitskollegen aufweisen.
Keywords: I26; J24; J31; 330; education; educational mismatch; wages; job mobility; training